Evaluation of the implementation of personalised outcomes forecasts to optimise supervised exercise therapy in patients with intermittent claudication: a multimethods process evaluation - Philip J van der Wees; Anneroos Sinnige; Thomas J Hoogeboom; Laura H M Marcellis; Andrew Kittelson; Steffie Spruijt; Joep A W Teijink; Anne G E van Bergen (BMJ Open Quality)
Background Personalised outcomes forecasts (POFs) were introduced among physical and exercise therapists in the Netherlands to optimise supervised exercise therapy for patients with intermittent claudication. Yet, therapists’ initial adoption and sustainable implementation of POFs can be influenced by various factors.Objectives The purpose of this study was to examine therapists’ adoption of the POFs, their fidelity to the measurement protocol for supervised exercise therapy, and their perceived barriers and facilitators for using POFs in practice.Methods A multimethod process evaluation was conducted, including quantitative descriptive and pre–post approaches, as well as a qualitative framework approach. To examine adoption, we evaluated the proportion of therapists who expressed interest in POFs by completing one of three provided e-learnings and the proportion of therapists who started using POFs in practice. To examine fidelity to the measurement protocol, we compared the per-episode proportion of follow-up measurements documented by therapists preimplementation and postimplementation. Qualitative data on barriers and facilitators were identified through semistructured interviews with therapists.Results One year after the implementation, 89% of therapists eligible to use POFs (n=1727) completed at least one e-learning and 51% of therapists started using POFs. The per-episode proportion of documented follow-up measurements per therapist increased, from a mean rate of 37% (3 months) and 22% (6 months) during the preimplementation period to a mean rate of 53% (3 months) and 32% (6 months) during the postimplementation period (p<0.001). Among interviewed therapists (n=12), identified barriers included competing demands and a lack of skills or confidence. Identified facilitators included the potential to improve the quality of care and a positive user attitude.Conclusions Our findings suggest that although there is initial interest in and adoption of POFs, addressing barriers and leveraging facilitators through tailored implementation strategies could further increase their utilisation in practice.